The effects of physical activity on adolescent psychological sub-health: chain-mediated effects of self-control and mobile phone addiction - Zhang Shuaishuai (BMC Psychology)
Abstract This research examines the link between physical activity (PA) and adolescent psychological sub-health (PSH), emphasizing the intermediary roles of self-control (SC) and mobile phone addiction (MPA). Utilizing the Physical Activity Rating Scale (PARS), SC Scale (SCS), MPA Tendency Scale (MPATS), and the Multidimensional Subhealth Questionnaire of Adolescents (MSQA), data were gathered from 1,052 adolescents. The findings indicate that (1) PA is negatively associated with both PSH and MPA, yet positively correlates with SC. Additionally, SC is inversely linked to PSH and MPA, whereas MPA is directly associated with PSH. (2) The analysis shows that SC and MPA partially mediate the impact of PA on PSH. (3) Moreover, both factors act as sequential mediators in the relationship between PA and PSH. These results enhance our understanding of the pathways through which physical activity influences adolescent PSH and offer important theoretical and practical perspectives for employing PA to boost adolescent mental health.